Politik Dinasti Dari Perspektif Demokrasi dan Hak Warga Negara Dalam Pemilihan Umum Di Indonesia - Marwenny, Elwidarifa; Syafwar, Robi; Permata, Gitra (Nagari Law Review, 2024)
The implementation of democracy in Indonesia is a mandate from the provisions of Article 2 paragraph (1) and Article 6A paragraph (1) of the 1945 Constitution of the Republic of Indonesia, where one of the indicators is general elections. However, the implementation of general elections is often overshadowed by the presence of family members of powerful politicians running for general elections and succeeding, including the elections for president, governor, regent, and others. This condition can trigger much debate and concern about democracy, the quality of elections, and political stability in Indonesia. Nevertheless, the right to elect and to be elected are protected rights and their existence is recognized by the constitution. The limitations of the problem in this paper include: 1) Political dynasty in the perspective of democracy; 2) Political dynasty in the perspective of democracy and citizens' rights in elections in Indonesia. This research used a normative juridical approach by using secondary data in the form of literature studies so that the conclusions are obtained that: a) political dynasty is contrary to democratic principles that emphasize transparency, accountability, and fair participation; b) although the regulations have been set up to protect citizens' rights to elect and be elected, the rise of political dynasty shows incompatibility with democratic principles. It is difficult to avoid political dynasty in a democracy, but efforts are needed to maintain balance and avoid abuse of power by the ruling family.